2017
DOI: 10.1039/c7ta06514k
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical multi-shelled nanoporous mixed copper cobalt phosphide hollow microspheres as a novel advanced electrode for high-performance asymmetric supercapacitors

Abstract: Hierarchical multi-shelled nanoporous mixed copper cobalt phosphide microspheres have been for the first time developed as a novel advanced electrode with superior electrochemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…These multishelled mixed metal oxides and phosphides were demonstrated to be promising electrode material candidates for asymmetric supercapacitor (ASC) devices. 152,153 In addition to metal oxides, metal sulfides have also been widely applied as supercapacitor electrodes. When compared to oxides, transition metal sulfides are expected to exhibit greater electric conductivity and better redox chemistry.…”
Section: Template-free Methodsmentioning
confidence: 99%
“…These multishelled mixed metal oxides and phosphides were demonstrated to be promising electrode material candidates for asymmetric supercapacitor (ASC) devices. 152,153 In addition to metal oxides, metal sulfides have also been widely applied as supercapacitor electrodes. When compared to oxides, transition metal sulfides are expected to exhibit greater electric conductivity and better redox chemistry.…”
Section: Template-free Methodsmentioning
confidence: 99%
“…This cuco 2 o 4 structure can provide more active sites for electrochemical reactions by nano pores and a high specific surface area that they can facilitate the access of the electrolyte. In the previous studies, the addition of p19 protein to the substrates was via synthetic or non-synthetic linkers 18,27 . For example, in the ramnani's research showed that the binding of p19 on the CNT/FET surface was via PBASE which it caused to reduce the resistance of the electrochemical substrate by covering the electrochemical reactions 28 .…”
Section: Resultsmentioning
confidence: 99%
“…In the Co 2p region (Figure c), the binding energies located at 778.8 and 779.3 eV can be assigned to the presence of Co 3+ and Co 2+ , respectively, in the Co 2p 3/2 spectrum. Similarly, the peaks at 793.3 and 794.2 eV in the Co 2p 1/2 spectrum also suggest coexistence of Co 2+ and Co 3+ . According to the XPS spectra of S 2p in Figure d, two characteristic peaks at 161.3 and 162.3 eV are ascribed to S 2p 3/2 and S 2p 1/2 , respectively.…”
Section: Resultsmentioning
confidence: 78%
“…Similarly,t he peaks at 793.3 and 794.2 eV in the Co 2p 1/2 spectrum also suggest coexistence of Co 2 + and Co 3 + . [34,35] According to the XPS spectra of S2 pi nF igure 2d,t wo characteristic peaks at 161.3 and 162.3 eV are ascribed to S2 p 3/2 and S 2p 1/2 ,r espectively.F urthermore, the magnitude of the peak splitting is approximately 1.0 eV,a nd weak satellitep eaks are located at 168.4 eV,i ndicating the priority of S 2À in CuCo 2 S 4 . [36,37] The peak at 163.3 eV corresponds to the typical metal-sulfur (CuÀSa nd CoÀS) bonds for S2 p 1/2 .…”
Section: Resultsmentioning
confidence: 99%